Efektivitas Pengendalian Internal Persediaan Obat-Obatan Penanggulangan Covid-19 Di Instalasi Farmasi Dinas Kesehatan Provinsi Jambi - Uni Mardhotillah; Diska Arliena Hafni (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This research aim to analyze effectiviness of internal control of Covid-19 medicine management avalibility at pharmaceutical installation of Jambi Health Departement. This research is case study research with qualitative approach. The results showed that the pharmaceutical installation of the Jambi Health Office had carried out internal controls well to protect its assets and efforts to increase its managerial activities. The Jambi Health Office Pharmacy Installation has implemented internal control based on COSO standards in managing supplies of special medicines for Covid-19 prevention properly and effectively. This can be proven by the fulfillment of the implementation of 13 indicators (87%) of the 15 COSO indicators that have been carried out by the Pharmaceutical Installation of the Jambi Health Office.